Swimming Upstream: Faculty and Staff Members From Urban Middle Schools in Low-Income Communities Describe Their Experience Implementing Nutrition and Physical Activity Initiatives - Katherine W. Bauer, SM; Aarti Patel; Lisa A. Prokop; S. Bryn Austin, ScD (Preventing Chronic Disease, 2006)
Introduction Addressing childhood overweight has become a top priority in the United States. Modification of school policies and practices has been used in an attempt to address the overweight epidemic among children and adolescents. Culturally diverse urban schools in low-income communities attempting to improve nutrition and increase physical activity may face unique challenges in the school environment. A better understanding is needed about school environments and how they may affect the implementation, efficacy, and sustainability of initiatives designed to improve nutrition and physical activity. Methods We carried out a qualitative study in five urban middle schools in low-income communities that had recently implemented Planet Health, a nutrition and physical activity intervention, to assess which aspects of the schools’ physical, social, and policy environments were facilitating or impeding the implementation of health promotion initiatives. Thirty-five faculty and staff members participated. We conducted one focus group per school, with an average of seven participants per group. We analyzed focus group transcripts using the thematic analysis technique to identify key concepts, categories, and themes. Results Teachers and staff members in our study identified many school-related environmental barriers to successful implementation of nutrition and physical activity initiatives in their schools. School personnel recommended that classroom-based nutrition interventions such as Planet Health be coordinated with school food services so that the healthy messages taught in the classroom are reinforced by the availability of healthy, culturally appropriate cafeteria food. They identified household food insufficiency and overly restrictive eligibility criteria of the federally subsidized meal program as critical barriers to healthy nutritional behaviors. They also identified weight-related teasing and bullying and unhealthy weight-control behaviors as challenges to promotion of healthy nutrition and physical activity. Conclusion To maximize intervention efforts, researchers and practitioners must consider the effects of school environments on nutrition and physical activity initiatives.